A Comparison of Traditional and Geometric Morphometric Techniques for the Study of Basicranial Morphology in Horses: A Case Study of the Araucanian Horse from Colombia (2023)
Skull size and shape have been widely used to study domestic animal populations and breeds. Although several techniques have been proposed to quantify cranial form, few attempts have been made to compare the results obtained by different techniques. While linear morphometrics has traditionally been used in breed characterization, recent advances in geometric morphometrics have created new techniques for specifically quantifying shape and size. The objective of this study was to compare two morphometric methods for their ability to describe external morphology. For this purpose, 20 skull specimens of adult male Araucanian horses were examined. Two age categories were established (the “mature group”, M3 not fully erupted to moderately worn, n = 7; and the “senile group”, M3 totally erupted and highly worn, n = 13). Both methods showed that there were statistical differences between generations, but discrimination rates were different between methods with the geometric morphometric analysis obtaining a rate of 97.5%. Although linear morphometrics was found to be compatible with geometric morphometrics, the latter was better able to discriminate the two groups and it also provides more information on shape. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.